Integration of Aesthetics and Creative Design: The influence of traditional Ru porcelain on product design - Siti Mastura Md Ishak; Bin Song; Nazlina Shaari; Velu Perumal (Environment-Behaviour Proceedings Journal, 2025)
This study reviews the historical background of Ru porcelain aesthetics, emphasizing its natural and minimalist qualities. It proposes the application of Ru porcelain aesthetics to modern product design, focusing on material selection, craftsmanship, incorporation of natural elements, and combining cultural heritage with innovation. The research deepens the understanding of the value of Ru porcelain aesthetics and its role in product integration and innovation, providing practical guidance and methodologies for its application in contemporary design practices.